Improved intratumoral penetration of IL12 immunocytokine enhances the antitumor efficacy - Jung, Keunok; Yoo, Sojung; Kim, Jung-Eun; Kim, Wook; Kim, Yong-Sung (Frontiers in Immunology, 2022)
Tumor-targeting antibody (Ab)-fused cytokines, referred to as immunocytokines, are designed to increase antitumor efficacy and reduce toxicity through the tumor-directed delivery of cytokines. However, the poor localization and intratumoral penetration of immunocytokines, especially in solid tumors, pose a challenge to effectively stimulate antitumor immune cells to kill tumor cells within the tumor microenvironment. Here, we investigated the influence of the tumor antigen-binding kinetics of a murine interleukin 12 (mIL12)-based immunocytokine on tumor localization and diffusive intratumoral penetration, and hence the consequent antitumor activity, by activating effector T cells in immunocompetent mice bearing syngeneic colon tumors. Based on tumor-associated antigen HER2-specific Ab Herceptin (HCT)-fused mIL12 carrying one molecule of mIL12 (HCT-mono-mIL12 immunocytokine), we generated a panel of HCT-mono-mIL12 variants with different affinities (KD) mainly varying in their dissociation rates (koff) for HER2. Systemic administration of HCT-mono-mIL12 required an anti-HER2 affinity above a threshold (KD = 130 nM) for selective localization and antitumor activity to HER2-expressing tumors versus HER2-negative tumors. However, the high affinity (KD = 0.54 or 46 nM) due to the slow koff from HER2 antigen limited the depth of intratumoral penetration of HCT-mono-mIL12 and the consequent tumor infiltration of T cells, resulting in inferior antitumor activity compared with that of HCT-mono-mIL12 with moderate affinity of (KD = 130 nM) and a faster koff. The extent of intratumoral penetration of HCT-mono-mIL12 variants was strongly correlated with their tumor infiltration and intratumoral activation of CD4+ and CD8+ T cells to kill tumor cells. Collectively, our results demonstrate that when developing antitumor immunocytokines, tumor antigen-binding kinetics and affinity of the Ab moiety should be optimized to achieve maximal antitumor efficacy.